PROBLEMS OF STATISTICAL RESEARCH OF CHILDREN IN DIFFICULT LIFE SITUATIONS - L. A. Davletshina; M. V. Karmanov; O. E. Bashina (Вестник университета)
The article considers the issues of statistical accounting of of persons of child age who have fallen into difficult life situation. The paper сarries out a comparison of the conceptual apparatus, revealing such a public category as “children” and gradation parameters of specified population groups from the point of view of revealing the object of study. The authors justify the need to characterize the subject of the study – a difficult life situation in which both an adult and a child can get, highlight particularly the age group “teenagers”. The study presents features of difficult life situations in which children and adolescents can get. The article lists the areas of occurrence of complex circumstances in which difficult life situations are formed and developed. Based on the analysis, the authors propose and substantiate an original system of indicators for assessing persons of child age who have fallen into a difficult life situation.